Characteristic Of The YTTRIA Stabilized Zirconia (YSZ) for Ceramic Injection Moulding by Using Palm Stearin as a Primary Binder / Mahfuzah Zainudin and Muhammad Hussain Ismail - Zainudin, Mahfuzah; Ismail, Muhammad Hussain (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Ceramic injection moulding (CIM) is a near net shape process to produce smaller and intricate parts at a competitive cost. However, fine particle size (nano scale) used for such injection moulding process generally leads to agglomeration, higher binder content and critical dimensional shrinkage, which result in defects on the sintered components. This study extensively investigates the characteristics of YSZ for CIM process. YSZ parts were moulded by CIM process that utilized a multi-component binder system using palm stearin (PS) and polyethylene (PE) in 60:40 (vol %) ratio. The powders were characterized using particle size analyzer, pycnometer density and scanning electron microscopic (SEM). The binders were characterized by the pycnometer density, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Powders loading were chosen by the critical powder volume percentage (CPVP) through an oil absorption test. YSZ powder was mixed with the binders at different powder loadings ranging from 58 to 60 vol% based on CPVP. The parts were injected moulded, thermal debound, pre-sintered and sintered. The microstructure, green strength and hardness of the sintered part at different powder loadings were investigated. A large porous region was clearly observed at 58 vol% compared to 60 vol%. All samples were sintered at 1350 ᴼC, with the highest green strength and hardness was 13MPa and 357.42 HV respectively were given by the sintered part at powder loading of 60 vol%.